Planting history and propagule pressure as predictors of invasion by woody species in a temperate region - Krivánek, Martin; Pysek, Petr; Jarosík, Vojtech (Conservation biology, 2006)
We studied 28 alien tree species currently planted for forestry purposes in the Czech Republic to determine the probability of their escape from cultivation and naturalization. Indicators of propagule pressure (number of administrative units in which a species is planted and total planting area) and time of introduction into cultivation were used as explanatory variables in multiple regression models. Fourteen species escaped from cultivation, and 39% of the variance was explained by the number of planting units and the time of introduction, the latter being more important. Species introduced early had a higher probability of escape than those introduced later, with more than 95% probability of escape for those introduced before 1801 and <5% for those introduced after 1892. Probability of naturalization was more difficult to predict, and eight species were misclassified. A model omitting two species with the largest influence on the model yielded similar predictors of naturalization as did the probability of escape. Both phases of invasion therefore appear to be driven by planting and introduction history in a similar way. Our results demonstrate the importance of forestry for recruitment of invasive trees. Six alien forestry trees, classified as invasive in the Czech Republic, are currently reported in nature reserves. In addition, forestry authorities want to increase the diversity of alien species and planting area in the country.
Keywords: Česká republika; stromy; ekosystém; Czech Republic; Forestry; Population Dynamics; Trees; populační dynamika; lesnictví; Ecosystem